2021
DOI: 10.1007/s11676-021-01358-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of density-related fine root production to soil and leaf traits in coniferous and broad-leaved plantations in the semiarid loess hilly region of China

Abstract: Fine roots are the most active and functional component of root systems and play a significant role in the acquisition of soil resources. Density is an important structural factor in forest plantations but information on changes in fine roots along a density gradient is limited. In this study, plantations of black locust (Robinia pseudoacacia L.) and Chinese pine (Pinus tabuliformis Carr.) with four density classes were analyzed for the influence of soil and leaf traits on fine root growth. Fine root biomass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…This indicates that the ecological stoichiometric characteristics of desert saline shrub leaves are not directly determined by the characteristics of soil nutrient contents, but are related to their own genetic characteristics, which reflects the unique adaptation mechanism of different desert halophyte shrubs to habitats [50], consistent with the results of Luo et al (2017) [51] and Song et al (2020) [52]. Under soil moisture-and nutrient-scarce conditions, Xinjiang desert halophyte shrubs have formed their own unique stoichiometric characteristics and physiological ecology, reflecting the relatively stable adaptability of desert saline shrubs to extreme environments [16]. The environmental indicators selected in this study are limited, and more environmental indicators will be combined in future studies to conduct a comprehensive analysis of the relationship between halophytes and environmental factors.…”
Section: Response Of Desert Halophyte Shrubs' Stoichiometry To Soil F...supporting
confidence: 83%
See 2 more Smart Citations
“…This indicates that the ecological stoichiometric characteristics of desert saline shrub leaves are not directly determined by the characteristics of soil nutrient contents, but are related to their own genetic characteristics, which reflects the unique adaptation mechanism of different desert halophyte shrubs to habitats [50], consistent with the results of Luo et al (2017) [51] and Song et al (2020) [52]. Under soil moisture-and nutrient-scarce conditions, Xinjiang desert halophyte shrubs have formed their own unique stoichiometric characteristics and physiological ecology, reflecting the relatively stable adaptability of desert saline shrubs to extreme environments [16]. The environmental indicators selected in this study are limited, and more environmental indicators will be combined in future studies to conduct a comprehensive analysis of the relationship between halophytes and environmental factors.…”
Section: Response Of Desert Halophyte Shrubs' Stoichiometry To Soil F...supporting
confidence: 83%
“…Secretohalophytes and pseudohalophytes had the highest C/N and C/P ratios, and they had higher carbon sequestration advantages in nutrient-poor habitats than euhalophytes [13]. Overall, C/N and C/P were high, which can be attributed to the extreme drought, high temperature, and strong evaporation in the study area [16,30]. To resist harsh environments, plants reduce their growth rate, resulting in relatively high C/N and C/P ratios in the leaves [32].…”
Section: Relationship Between Ecological Stoichiometric Characteristi...mentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, increased surface litter buildup over time can lead to greater OM and/or TN levels at the 0-10 cm soil depth, regardless of thinning intensity. A study also found that soil nutrient status (e.g., N) was related to fine root necromass in pine plantations [53]. The fine root distribution pattern is controlled by soil resource availability, with a positive correlation reported with soil organic carbon [54].…”
Section: Vertical Distribution Patterns Of Fine Root Biomass and Necr...mentioning
confidence: 93%
“…Before the "Grain for Green" project, there should be little difference in soil nutrients between the plantations due to the long-term cultivation of the cropland under similar fertilization management [51]. After replacing the cropland, the forest vegetation would change soil nutrient types and distribution gradually by changing the decomposition input of the litter, fine root yield and turnover rate [66,67]. Disparities in soil nutrients between different stand densities may gradually develop.…”
Section: Effect Of Stand Density On Soil Nutrients In These Plantatio...mentioning
confidence: 99%